The economics of quarantine and the SPS Agreement - Anderson, Kym; McRae, C. F. (Cheryl F.); Wilson, David (David William), 1947- (University of Adelaide Press, 2012)
This collection resulted from an international workshop funded and organised by Biosecurity Australia, the agency of government responsible for analysing Australia's quarantine import risks and for negotiating multilateral SPS rules and less restrictive access to overseas markets for Australian produce. The workshop, which was held at the Melbourne Business School on 24-25 October 2000, brought together a distinguished group of applied economists and quarantine policy analysts whose focus involves regions as disparate as Europe, North America, Africa, Asia and New Zealand, in addition to Australia.